2014
DOI: 10.1038/ejcn.2014.3
|View full text |Cite
|
Sign up to set email alerts
|

Plant sterol and stanol intake in Finland: a comparison between users and nonusers of plant sterol- and plant stanol-enriched foods

Abstract: The intake of PS can reach several grams in a subgroup of subjects consuming PS-enriched foods. The manufacturers' recommendations on PS-enriched food consumption are not consistently followed, and customer guidance needs to be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The stanols can be produced by the hydrogenation of plant sterols [31]. In Finland, as an example, the natural dietary intake of phytosterols is about 300 mg/day [32,33]. Plant stanols, again, represent a very low share of the phytosterols; their daily natural intake is only about 20 mg [32,33].…”
Section: Cholesterol-lowering Diet Compared With Dietary Interventmentioning
confidence: 99%
“…The stanols can be produced by the hydrogenation of plant sterols [31]. In Finland, as an example, the natural dietary intake of phytosterols is about 300 mg/day [32,33]. Plant stanols, again, represent a very low share of the phytosterols; their daily natural intake is only about 20 mg [32,33].…”
Section: Cholesterol-lowering Diet Compared With Dietary Interventmentioning
confidence: 99%
“…The same concerns plant sterols. For example, a Finnish study showed that more than half of the users of foods with added plant stanol or plant sterol ester did not reach the recommended daily intake [ 44 ]. Another example is a survey on consumer purchase behaviour which included 91,000 households in the Netherlands, Belgium, United Kingdom, France, and Germany [ 45 ].…”
Section: Optimal Use Of Plant Stanol Estermentioning
confidence: 99%